Occurrence of Loranthus Spp. On Oak in Kumaun Himalaya - Ginwal, H. S.; Rawat, P. S.; Dubey, R. C.; Singh, R. P. (Indian Forester, 1994)
Occurrence and infection intensity of Loranthus spp. On four species of Quercus viz. Q. floribunda,Q. lanuginose, Q. leucotrichophora and Q. semecarpifolia were studied in Naintal of Kumaun Himalaya. Occurrence of the parasite was maximum in Q. floribunda and minimum in Q. lanuginosa. In no case Q. semecarpifolia was found infected. Infected was absent in seedling and saplings but manifested with increasing severity with tree age.